ANALISIS NORMATIF UNDANG-UNDANG NO. 1 TAHUN 2013 TENTANG LEMBAGA KEUANGAN MIKRO (LKM) ATAS STATUS BADAN HUKUM DAN PENGAWASAN BAITUL MAAL WAT TAMWIL (BMT) - Nurulita Aryani; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research was conducted with the aim to find out how the status of legalentities and supervision of BMT before and after the existence of Law No. 1 of2013 concerning Microfinance Institutions (MFIs).The sample used in this study was BMT-Maslahah Sidogiri. The method usedis a qualitative descriptive analysis method, which analyzes the data that has beencollected by synchronizing with the regulations contained in Law Number 1 of2013 concerning Microfinance Institutions (MFIs), so that later it will be knownwhere the supervision is.Based on the results of the analysis it can be seen that before the Law No. 1of 2013, BMT-Maslahah Sidogiri is in the form of a cooperative and has the legalstatus of the Islamic Financial Services Cooperative and its supervision is subjectto the Minister of Cooperatives and SME Regulation No. 39 / Per / M.KUKM / XII/ 2007. While after the Act No. 1 of 2013, BMT-Maslahah Sidogiri still chooses toform a cooperative so that its supervision remains under the Minister ofCooperatives and SME Regulation No. 39 / Per / M.KUKM / XII / 2007.Keywords: Status of Legal Entity, Supervision, Act No.1 of 2013 concerningMicrofinance Institutions.